Chapter 5 A math-avoidant profession? Review of the current research about early childhood teachers' mathematics anxiety and empirical evidence - Jenßen, Lars (Taylor & Francis, 2021)
Despite positive attitudes towards mathematics, it must be assumed that mathematics anxiety is a factor not to be underestimated in (pre-service) early childhood teachers. In the first part, this article reviews the current international state of research on early childhood teachers' mathematics anxiety and shows the achievements and limitations of previous studies. The majority of the reviewed studies deals with pre-service early childhood teachers and their teacher education. Only a few studies tried to relate in-service early childhood teachers' mathematics anxiety and children's mathematical achievement. In the second part, this contribution examines empirically whether it can be assumed that the profession "early childhood teacher" can be characterized as "math-avoidant". For this purpose, n = 774 German pre-service early childhood teachers were examined with regard to their mathematics anxiety and their choice of career. The results indicate effects of mathematics anxiety on the intentional choice to work as an early childhood teacher. The paper concludes with a general conclusion on the importance of mathematics anxiety for early childhood teachers' professional competence and an outlook on future research.